Virtue and vulnerability: Discourses on women, gender and climate change - Arora-Jonsson, Seema (Global Environmental Change, 2011)
In the limited literature on gender and climate change, two themes predominate – women as vulnerable or virtuous in relation to the environment. Two viewpoints become obvious: women in the South will be affected more by climate change than men in those countries and that men in the North pollute more than women. The debates are structured in specific ways in the North and the South and the discussion in the article focuses largely on examples from Sweden and India. The article traces the lineage of the arguments to the women, environment and development discussions, examining how they recur in new forms in climate debates. Questioning assumptions about women's vulnerability and virtuousness, it highlights how a focus on women's vulnerability or virtuousness can deflect attention from inequalities in decision-making. By reiterating statements about poor women in the South and the pro-environmental women of the North, these assumptions reinforce North–South biases. Generalizations about women's vulnerability and virtuousness can lead to an increase in women's responsibility without corresponding rewards. There is need to contextualise debates on climate change to enable action and to respond effectively to its adverse effects in particular places.
Keywords: 2000 à aujourd'hui; approches et analyses; discours dominant; environnement; projet charge mentale; périodes historiques; relations nords/suds; ressource en ligne; santé; systèmes d'oppressions; thématiques; vulnérabilité